Web-based interventions to improve blood pressure control in patients with hypertension: a protocol for a systematic review - Matilde Monteiro-Soares; Inês Rosendo; Maria Leonor Bernardes; Beatriz Rosendo-Silva (BMJ Open)
Introduction Hypertension is the major cause of cardiovascular disease and mortality in the world. Blood pressure control (BPC) is recognised as a key measure in the management of hypertension. Several studies have been conducted assessing the impact of specific web-based interventions in improving BPC. Our systematic review intends to identify all the available web-based interventions and determine if and which are more effective than usual care in improving BPC.Methods and analysis We will include randomised control trials completed until April 2023 including patients diagnosed with hypertension comparing the effect of receiving usual care versus web-based interventions in BPC. No language restriction will be applied. We will start with an extensive electronic database search, in the Cochrane Central Register of Controlled Trials, PubMed, Embase, Scopus, EU Clinical Trials Register, Pan-African Clinical Trials Registry and ClinicalTrials.gov. Eligibility criteria will be applied blindly and independently by two researchers to the title and abstract of the references, in the first stage, and to the full version of the ones selected. All divergences will be solved by a third researcher. We will conduct a narrative description and meta-analysis (if adequate) of the results of the included studies, structured according to the type of intervention, characteristics of the population and outcome measurement. We will extract features of the web-based interventions, selecting the ones with the best outcomes regarding BPC, to later propose an ideal web-based intervention to improve BPC in hypertensive patients and/or guide future research on this topic. The risk of bias will be assessed using Cochrane’s RoB2 Tool.Ethics and dissemination Ethical approval is not required since this is a protocol for a systematic review. The findings of this study will be disseminated through peer-reviewed publications and national or international conference presentations. Updates of the review will be conducted, as necessary.PROSPERO registration number PROSPERO CRD42020184166.